No way out: precarious living in the shadow of poverty and drug dealing - Duck, Waverly (The Univ. of Chicago Press, 2015)
Introduction : precarious living -- Jonathan's world -- Drug-dealing careers -- The rise and fall of Lyford Street -- Snitching, gossip, and the power of information -- The politics of murder and revenge -- Collective punishment : black men's reflections on everyday life in Bristol Hill -- Benita's story : coping with poverty in the age of welfare reform -- Conclusion : understanding everyday life in the shadow of poverty and drug dealing